The Nineteen Seventy One (1971) Indo-Pak War : A Soldier's Narrative - Qureshi, Hakeem Arshad, Maj. Gen. (Karachi Oxford University Press, 2012)
This is an eyewitness account of the political and military upheaval in East Pakistan in 1971, which was in the grip of Bangla nationalism. The book covers the period from general elections in December 1970 to the break up of Pakistan in December 1971. Its main focus is on the 1970 elections and the subsequent developments, the civil disobedience movement and its transformation into insurgency, Pakistan's efforts to cope with the insurgency, India's intervention and the full-fledged invasion, the war and the aftermath.
Include Annexures, Bibliography and Index.
A Soldier's Narrative.
Keywords: India-Pakistan Conflict (1971) -- Bangladesh -- Revolution (Bangladesh : 1971) -- Pakistan